Techno-Stress of the Faculty Members in a Higher Education Institution: Basis for a Faculty Development Program - Espiritu, Cecile de Mesa (JPAIR Institutional Research, 2022)
Technology is one of the greatest inventions of humankind, which is utilized in all sectors of society.  Teachers' integration of technology leads them to facilitate and enhance the teaching-learning process.  Teachers must develop their competence to use these with ease and confidence. The abrupt transition to online learning has significantly changed the learning experiences. Teachers are pressured to adapt to technological trends. The inability to adapt to technology may lead to techno-stress, a modern adaptation disorder due to failure to cope with technologies. The study adopted the descriptive method with 57 full-time and 110 part-time teacher-respondents.  The data were analyzed through frequency, percentage, weighted mean, t-test, ANOVA, and Pearson r. The findings show that most faculty members are integrating technology into teaching activities, using it for more than 5 hours a week. They had moderate levels of techno-stress in the learning-teaching process and social and technical issue orientations, while they had low-stress levels in professional and personal orientations. There is a significant relationship between technology usage and the assessed level of techno-stress of the teacher-respondents.   Counter-measures against techno-stress must be developed through a faculty development program with activities on stress, mental health issues, and technology adaptation.
Keywords: Social Science; technology integration; descriptive method; Pasig City; Philippines